2017
DOI: 10.1177/1753193417726051
|View full text |Cite
|
Sign up to set email alerts
|

Rising incidence of scaphoid fracture surgery in Finland

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…However, plate fixation and external fixation (procedures seldom used for fixation of the scaphoid, but rather for distal radius fractures), were included in the analyses, and this might result in an over-estimation of the incidence of surgery. In accordance with Raittio et al. (2018), we found that men were operated on more often than women.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, plate fixation and external fixation (procedures seldom used for fixation of the scaphoid, but rather for distal radius fractures), were included in the analyses, and this might result in an over-estimation of the incidence of surgery. In accordance with Raittio et al. (2018), we found that men were operated on more often than women.…”
Section: Discussionsupporting
confidence: 82%
“…The rate of surgical interventions for scaphoid fractures was unchanged between 2006 and 2015. In contrast, Raittio et al. (2018) reported increased incidence of scaphoid fracture surgery in Finland 1997–2014.…”
Section: Discussionmentioning
confidence: 94%
“…Because scaphoid fractures are more likely to occur in younger patients, their estimated incidence may have been lower due to inclusion of older patients (and conversely, our estimated incidence density may have been higher due to exclusion of patients over age 65 years). While our estimate of scaphoid fracture incidence is lower than that of population-based reports from other countries [9,13,15,17], the differences in injury epidemiology, population demographics, and health care delivery systems among countries preclude meaningful direct comparison. In a recent population-based study in Finland, trends in surgical treatment of scaphoid fractures and nonunion were evaluated [17].…”
Section: Discussionmentioning
confidence: 56%
“…While our estimate of scaphoid fracture incidence is lower than that of population-based reports from other countries [9,13,15,17], the differences in injury epidemiology, population demographics, and health care delivery systems among countries preclude meaningful direct comparison. In a recent population-based study in Finland, trends in surgical treatment of scaphoid fractures and nonunion were evaluated [17]. The authors did not investigate the rate of non-operative scaphoid fracture treatment, which likely explains why their estimated incidence of scaphoid fracture primary fixation (5.5 to 17.8 cases per 1,000,000 person-years) differs from the 10.6 fractures treated per 100,000 person-years observed in the current study.…”
Section: Discussionmentioning
confidence: 56%
“…The early fixation of scaphoid fractures seems attractive and its popularity is increasing. 6 Many small studies have compared operative and nonoperative treatment. 1,[7][8][9][10][11]27,28 many clinicians advocate surgical treatment citing improved function, quicker return to normal activities, and increased rate of union based on this literature.…”
Section: Discussionmentioning
confidence: 99%